Human-Centered Adaptive Leadership and Organizational Resilience in the Era of Digital Transformation: A Decade of Integrative Review and Future Research Agenda - Saputra, Julian Eka (Generate Digital Publishing, 2025)
Objective: Despite the growing literature on adaptive leadership in digitally transforming organizations, research remains fragmented and largely technology-focused, providing limited understanding of its role in supporting human-centered organizational resilience. This study synthesizes two decades of adaptive leadership research and reframes adaptive leadership as a key human-centered HR capability that enables organizational resilience, learning, and employee agency in the digital era. Research Design & Methods: Using a bibliometric review of 65 Scopus-indexed articles, this study analyzes publication trends, disciplinary convergence, keyword co-occurrence, collaboration networks, and thematic evolution. Network mapping and frequency-based visualization are employed to uncover dominant conceptual trajectories and underexplored human-centered dimensions within the adaptive leadership literature. Findings: The findings show a rapid growth of adaptive leadership research since 2020, alongside intensified digital transformation. Although adaptive leadership is increasingly linked to organizational resilience and strategic agility, human and HR-related aspects—such as sensemaking, collective learning, employee adaptability, and psychosocial resources—remain underdeveloped and insufficiently integrated into existing theories. The analysis also suggests a growing recognition of adaptive leadership as a systemic and relational capability, yet its implications for human-centered HR design are still not clearly articulated. Implications & Recommendations: This study encourages future research to move beyond techno-centric approaches by integrating adaptive leadership with human-centered HR perspectives, particularly in relation to employee agency, ethical decision-making, and sustainable people management in digital contexts. Contribution & Value Added: This study contributes theoretically by reframing adaptive leadership as a human-centered HR capability rather than a purely strategic or technological response. By synthesizing fragmented literature and outlining a human-centered research agenda, it advances adaptive leadership theory and supports the development of idealistic HR practice in the digital era.